Amylase-assisted green synthesis of silver nanocubes for antibacterial applications. Issue 3 (4th December 2018) - Pandey, Anamika; Shankar, Shiv; Shikha,; Arora, Naveen Kumar
Abstract : In the present study, a bacterium producing alpha-amylase (Enzyme Commission number 3.2.1.1), Pseudomonas sp. (National Center for Biotechnology Information accession number KY548391.1), was isolated from decaying tea waste. The bacterium produced 15 U/ml amylase under submerged culture condition. Partially purified alpha-amylase (30 U/ml) from this bacterium was used to synthesize silver nanoparticles (AgNPs). The bioinspired synthesis of AgNPs was confirmed by ultraviolet–visible (UV–Vis) spectroscopy, Fourier transform infrared (FTIR) spectroscopy and scanning electron microscopy–energy-dispersive X-ray spectroscopy (SEM-EDX) techniques. UV–Vis studies revealed a surface plasmon peak at 435 nm, suggesting the amylase-mediated synthesis of AgNPs. FTIR analysis showed peaks indicating the presence of a thiol group in cysteine and carbonyl groups of amino acid residues and peptides of proteins interacting with silver nitrate responsible for stabilization of AgNPs. SEM confirmed the formation of polydispersed AgNPs that had diameters ranging from 63 to 142 nm and a cubical shape. The EDX spectrum showed a higher percentage of silver (84·09%) signal. Synthesized nanoparticles showed excellent antibacterial activity against multidrug-resistant bacterium Staphylococcus aureus . The present study proposes the advanced application of alpha-amylase in the synthesis of AgNPs and endorses them as an effective antibacterial agent against human pathogenic bacteria such as S. aureus .